Overview on the treatment of severe bronchial asthma - Giulio Dinardo; Cristiana Indolfi; Angela Klain; Chiara Lucia Bencivenga; Serena Ferrara; Fabio Decimo; Michele Miraglia del Giudice (Elsevier, 2024)
Childhood asthma, often linked with atopic conditions, poses a challenge when classified as severe and uncontrolled. The 2023 GINA guidelines define severe asthma in children as asthma that remains uncontrolled despite optimized treatment with high-dose ICS-LABA or requires high-dose ICS-LABA to prevent it from becoming uncontrolled. This category encompasses about 5% of pediatric asthma cases, emphasizing the need for innovative therapeutic exploration. Advances in understanding asthma phenotypes and endotypes enable personalized treatment based on biomarkers. Monoclonal antibodies offer targeted solutions, reducing exacerbations, improving lung function, and minimizing corticosteroid use in pediatric patients. Integrating these therapies requires a personalized approach by healthcare providers, enhancing outcomes in severe and refractory cases.